Identification of pathological-related and diagnostic potential circular RNAs in Stanford type A aortic dissection - Liang, Qiao; Zhou, Zeyi; Li, Hui; Tao, Qing; Wang, Yali; Lin, Anqi; Xu, Jing; Zhang, Bin; Wu, Yongzheng; Min, Haiyan; Wang, Lei; Song, Shiyu; et al. (Frontiers in Cardiovascular Medicine, 2023)
Stanford type A aortic dissection (TAAD) is one of the lethal macrovascular diseases caused by the invasion of blood into the media layer of ascending aortic wall. Inflammation, smooth muscle dysfunction, extracellular matrix (ECM) degradation were regarded as the major pathology in affected tissue. However, the expression pattern and its regulation especially through circular RNAs (circRNAs) as an overall characteristic of TAAD molecular pathology remain unclear. In the present study, we employed CIRCexplorer2 to identify circRNAs based on the RNA sequencing (RNA-seq) data of human ascending aortic tissues to systematically assess the role of circRNA in the massive alterations of gene expression in TAAD aortas. Lasso model determined 4 key circRNAs, namely circPTGR1 (chr9:114341075-114348445[-]), circNOX4 (chr11:89069012-89106660[-]), circAMN1 (chr12:31854796-31862359[-]) and circUSP3 (chr15:63845913-63855207[+]), which demonstrated a high power to discriminate between TAAD and control tissues, suggesting that these molecules stand for a major difference between the tissues at gene regulation level. Functionally, the competing endogenous RNAs (ceRNA) network of circRNA-miRNA-mRNA predicted by the circBank, TargetScan and other online databases, combining gene set enrichment analysis (GSEA) and cell component prediction, revealed that the identified circRNAs covered all the aspects of primary TAAD pathology, centralized with increasing inflammatory factors and cells, and ECM destruction and loss of vascular inherent cells along with the circRNAs. Importantly, we validated the high concentration and diagnostic capability of the 4 key circRNAs in the peripheral serum in TAAD patients by real-time polymerase chain reaction (RT-PCR). Thus, this study reinforces the vital status of circRNAs in TAAD and possibility of serving as promising diagnostic biomarkers and therapeutic targets.